Associations between Eating Behavior and Dietary Intake in a Sample of Type 2 Diabetes Patients - Lidia Iuliana Arhire; Ana Maria Gal; Andreea Gherasim; Otilia Nita; Alina Delia Popa; Laura Mihalache; Mariana Graur (Proceedings)
Type 2 diabetes mellitus (T2DM) is a multifactorial chronic condition which is profoundly influenced by dietary interventions. Unfortunately, these interventions often fail to produce the expected results due to the multiple determinants of food choice, with eating behavior having a large contribution. The aim of this study was to evaluate how eating behavior affects dietary intake in a population of patients with T2DM using validated tools. We conducted a cross-sectional quantitative study on a sample of patients with T2DM, assessing dietary intake using the validated EPIC food frequency questionnaire and evaluating eating behavior using the previously validated Dutch Eating Behavior Questionnaire (DEBQ). We used statistical analysis to generate correlations between the three variants of eating behavior obtained from the DEBQ (emotional, external and restrained eating) and dietary intake. In the study population of 416 diabetes patients, the average age was 62.64 ± 9.93 years, and 43.3% (n = 180) were men. Emotional eaters and external eaters showed a significantly higher intake of calories, lipids, nonalcoholic beverages (in women) and alcohol (in men). There were no correlations between restrained eating and dietary intake. Healthy eating is an important therapeutic intervention in T2DM, and our data suggest that understanding eating behavior could facilitate more individualized nutritional recommendations, but further studies are required.